RANCANG BANGUN INSTRUMENTASI INFRARED OBSTACLE AVOIDANCE SENSOR PADA DYNAMOMETER PRONY BRAKE DENGAN SISTEM MONITORING BERBASIS IOT (INTERNET OF THINGS) - Althesa Androva; Agus Mukhtar; Lutfianto Lutfianto (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Dynamometer is a test tool used to measure the torque of the motor. There are several types of dynamometers currently available, including Prony Brake dynamometers, Water Brake dynamometers, Rope Brake dynamometers, Eddy Current dynamometers, and Motor Generator dynamometers. In this thesis the researcher uses the Prony Brake Dynamometer system. The working principle of Prony Brake is to use the braking principle. Braking is done by adjusting the gas handle which presses the disc brake dynamometer which rubs against the motorbike's disc brake. The purpose of this research is to design and realize a Prony Brake type motor torque meter equipped with a sensor as a reading of the engine rotational speed value. As for what is produced in this study is the design of electrical Infrared sensors can work in accordance with the objectives in the formulation of this thesis problem. It is proven that the infrared sensor can read the rotary speed value of the prony break dynamometer engine and can send the results of that value to the Thinger.io web.